\(\left(x-1\right)^3+x^3+\left(x+1\right)^3=\left(x+2\right)^3\)
\(\Leftrightarrow x^3-3x^2+3x-1+x^3+x^3+3x^2+3x+1-x^3-6x^2-12x-8=0\)
\(\Leftrightarrow2x^3-6x^2-6x-8=0\)
\(\Leftrightarrow2.\left(x^3-3x^2-3x-4\right)=0\)
\(\Leftrightarrow x^3-4x^2+x^2-4x+x-4=0\)
\(\Leftrightarrow x^2.\left(x-4\right)+x.\left(x-4\right)+\left(x-4\right)=0\)
\(\Leftrightarrow\left(x-4\right).\left(x^2+x+1\right)=0\)
Mà \(x^2+x+1=\left(x+\dfrac{1}{2}\right)^2+\dfrac{3}{4}>0\)
\(\Rightarrow x-4=0\Leftrightarrow x=4\)